“We just do us”: Exploring the Language Use and Cultural Identity of Intercultural Couples in Auckland - Moore, Sophie (Auckland University of Technology, 2022)
The growing diversity in multicultural Auckland suggests a growing number of intercultural intimate relationships. Existing New Zealand studies have discussed how the rise in such relationships can threaten language maintenance and impact cultural identity in minority and migrant language communities. Yet, few studies have looked in to these issues from the perspectives of intercultural couples themselves. This research investigates the sociolinguistic attitudes, practices and cultural perspectives of Auckland-based couples to explore how language and cultural experiences impact their everyday life with others, their relationship dynamics and their construction of identity. This qualitative inquiry generated its primary data through semi-structured interviews conducted with six couples, of which one partner of each couple was a LOTE (Language other than English) background migrant and the other was an English-speaking background (ESB) New Zealand-born. Demographic questionnaires provided context to the interview data, and a researcher journal informed the theme-based analysis. Interview data showed that couples downplayed cultural differences and engaged in talk focused on their similarities, shared values and their individual personalities. Couples all have their own unique way of communicating and negotiating their cultural and linguistic selves, in-between cultures, in their everyday lives. At the same time, key common aspects identified across all participants’ communities of practice were humour, conscious communication, translanguaging and creative language play. Findings signalled the ability for partners to (re)construct their identity in the other language and culture. This often occurs through the use of humour, which is pragmatically and semantically challenging. This study goes beyond focusing only on linguistic and cultural differences, and highlights the diverse experiences of individuals, as well as evolving patterns of language and communication in intercultural communities of practice. It also underscores the need to address prevailing monolingual attitudes and cultural constructs in the host society, which undermine individual authenticity, belonging and connection. The experiences reported by couples in this study indicate the value and importance of LOTE learning and plurilingual education for fostering a more inclusive culture.
Keywords: Intercultural relationship; Identity; Language; Humour